ANALISA KEPEMIMPINAN KEPALA SEKOLAH DAN KINERJA GURU PENGARUHNYA TERHADAP PENINGKATAN MUTU LULUSAN PADA SEKOLAH DASAR PERMATA HARAPAN BATAM - Setiawan, Joko (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2018)
This research to analyze how much influence the quality improvement of graduates influenced by principal leadership and teacher performance. In conducting the analysis, measurement of multiple linear regression analysis using SPSS 22 program. This research resulted that principal leadership influence on dependent variable, that is the quality of graduates, the increase of teacher performance influence to the quality of the graduates. Based on the simultaneous test results, it can be seen that the independent variables are the level of Leadership Principal and Performance Teachers significant effect on the dependent variable, namely the quality of graduates seen in the final grade of graduates